2006
DOI: 10.1007/s11051-006-9097-2
|View full text |Cite
|
Sign up to set email alerts
|

Flame spray synthesis under a non-oxidizing atmosphere: Preparation of metallic bismuth nanoparticles and nanocrystalline bulk bismuth metal

Abstract: Metallic bismuth nanoparticles of over 98% purity were prepared by a modified flame spray synthesis method in an inert atmosphere by oxygen-deficient combustion of a bismuth-carboxylate based precursor. The samples were characterized by X-ray diffraction, thermal analysis and scanning electron microscopy confirming the formation of pure, crystalline metallic bismuth nanoparticles. Compression of the asprepared powder resulted in highly dense, nanocrystalline pills with strong electrical conductivity and bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…The combustion of carboxylate precursors under inert atmospheres has shown that the particle size distribution was preserved as in the case of metal oxide and salt nanoparticles and could be described as log-normal resulting in spherical particles with standard geometric deviations of σ = 1.5 (Grass and Stark 2006a) indicating that the inert (low oxygen concentrations) conditions do not affect the physical processes of nucleation, growth and aggregation. Latter has been further confirmed by the experimental observation of Grass and Stark (2006b) where the combustion of a bismuth precursor under various precursor flow rates and constant fuel to oxygen ratio resulted in metal nanoparticles with unchanged sizes similar to previous studies on the formation of metal oxides. Only dilution of the precursor resulted in a significant decrease of the powder mean particle size due to smaller particle concentration in the flame.…”
Section: Reducing Flames: From Oxides To Metal Nanoparticlessupporting
confidence: 83%
“…The combustion of carboxylate precursors under inert atmospheres has shown that the particle size distribution was preserved as in the case of metal oxide and salt nanoparticles and could be described as log-normal resulting in spherical particles with standard geometric deviations of σ = 1.5 (Grass and Stark 2006a) indicating that the inert (low oxygen concentrations) conditions do not affect the physical processes of nucleation, growth and aggregation. Latter has been further confirmed by the experimental observation of Grass and Stark (2006b) where the combustion of a bismuth precursor under various precursor flow rates and constant fuel to oxygen ratio resulted in metal nanoparticles with unchanged sizes similar to previous studies on the formation of metal oxides. Only dilution of the precursor resulted in a significant decrease of the powder mean particle size due to smaller particle concentration in the flame.…”
Section: Reducing Flames: From Oxides To Metal Nanoparticlessupporting
confidence: 83%
“…Similarly, by introducing a metal precursor with the fuel, nanoparticles may be synthesized in a fuel-rich, reduced-oxygen environment, offering the potential for producing transition metal oxides with a reduced oxidation state. Other studies using flame spray systems have demonstrated that by maintaining a reducing atmosphere, reduced metal oxides or even pure metals can be synthesized (Grass and Stark 2006a; b). Our focus is the magnetic iron oxide, magnetite (Fe 3 O 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have been known to enhance electroanalytical properties in some areas, primarily due to their increased surface area coupled with enhanced mass transport effects [36,37]. Though there have been many attempts to synthesize Bi nanoparticles, problems have often arisen in terms of contamination by surfactants [38,39], the presence of matrices [40] or more commonly the formation of bismuth oxides [41]. Bismuth oxides readily form in aerated water [42], and can significantly impede the electroactivity of Bi nanoparticles [41], thus a method to simply produce pure Bi nanoparticles that have a readily renewable surface, is highly desirable.…”
Section: Introductionmentioning
confidence: 99%